Surgical, clinical, and radiological outcomes of occipitocervical fusion using the plate–screw–rod system with allograft in craniocervical instability - Upadhyaya, Mihir (J Craniovertebr Junction Spine, 2019)
OBJECTIVE: We evaluated surgical, clinical, and radiological outcomes of posterior occipitocervical fusion (OCF) using plate–rod–screw construct supplemented with allograft in cases of occipitocervical instability. STUDY DESIGN: This was a retrospective analysis of prospective collected data. METHODS: Data of 52 patients who underwent posterior OCF using plate–screw–rod construct supplemented with allograft at a single institute from 2009 to 2014 were analyzed. Demographics, clinical parameters (Visual Analog Score [VAS], ODI, and mJOA score), functional status (McCormick scale), radiological parameters – mean atlantodens interval, posterior occipitocervical angle, occipitocervical 2 angle, and surgical parameters (operative time, blood loss, hospital stay, and fusion) with complications were evaluated. RESULTS: The mean age of the patients was 54.56 ± 16.21 years with male: female was 28:24. The mean operative time was 142.2 min (90–185 min) and mean blood loss was 250.8 ml. The mean duration of hospital stay was 6.7 days and mean follow-up period was 65.17 ± 5.39 months. There was significant improvement in clinical parameters (modified JOA score, VAS, and Oswestry Disability Index values) postoperatively. Forty patients showed recovery in neurological status at least in Grade 1 in McCormick scale with no neurological deterioration in any patient. Furthermore, radiological parameters at cervicomedullary junction got into acceptable range. Implant-related complications noted in 1 patient and 1 patient had vertebral artery injury. We had dural tear in 3 patients and infection in 2 patients. Fusion was achieved in 46 cases with mean time for fusion was 11.039 months. CONCLUSION: Patients with occipitocervical instability can successfully undergo posterior OCF using plate–screw–rod construct supplemented with allograft with high fusion rate, good clinical and functional outcomes, and low complication rate.